Alumina: discriminative analysis using 3D correlation of solid-state NMR parameters - Chandran, C Vinod; Kirschhock, Christine E A; Radhakrishnan, Sambhu; Taulelle, Francis; Martens, Johan A; Breynaert, Eric (Chemical Society reviews, 2019)
Synthetic transition aluminas (χ, κ, θ, γ, δ, η, ρ) exhibit unique adsorptive and catalytic properties leading to numerous practical applications. Generated by thermal transformation of aluminium (oxy)hydroxides, structural differences between them arise from the variability of aluminium coordination numbers and degree of dehydroxylation. Unequivocal identification of these phases using X-ray diffraction has proven to be very difficult. Quadrupolar interactions of 27Al nuclei, highly sensitive to each site symmetry, render advanced 27Al solid-state NMR a unique spectroscopic tool to fingerprint and identify the different phases. In this paper, 27Al NMR spectroscopic data on alumina reported in literature are collected in a comprehensive library. Based on this dataset, a new 3D correlative method of NMR parameters is presented, enabling fingerprinting and identification of such phases. Providing a gold standard from crystalline samples, this approach demonstrates that any sort of crystalline, ill crystallized or amorphous, mixed periodic or aperiodically ordered transition alumina can now be assessed beyond the current limitations of characterisation. Adopting the presented approach as a standard characterisation of alumina samples will readily reveal NMR parameter-structure-property relations suitable to develop new or improved applications of alumina. Methodological guidance is provided to assist consistent implementation of this characterisation throughout the fields involved.